If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 9 = 73 + -2x Reorder the terms: 9 + 6x = 73 + -2x Solving 9 + 6x = 73 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 9 + 6x + 2x = 73 + -2x + 2x Combine like terms: 6x + 2x = 8x 9 + 8x = 73 + -2x + 2x Combine like terms: -2x + 2x = 0 9 + 8x = 73 + 0 9 + 8x = 73 Add '-9' to each side of the equation. 9 + -9 + 8x = 73 + -9 Combine like terms: 9 + -9 = 0 0 + 8x = 73 + -9 8x = 73 + -9 Combine like terms: 73 + -9 = 64 8x = 64 Divide each side by '8'. x = 8 Simplifying x = 8
| 2x=5x-3 | | -6a+4=-2 | | 8+1x=8x | | 4+3x=-8 | | 2.1=4.5-6i | | 5(2x-1)-7x=7 | | (-2+7i)+(-4-5i)=0 | | 4x+34=7x+10 | | (5v+6)(7+v)=0 | | 8(x+1)=4x+4 | | 0-4x=9-7x | | 3y+2x= | | 72-6x=7x+20 | | 4y+6=-2 | | 6x+27=16x-83 | | -7-13x+7x=-14x+3-10 | | -5x^2-25=0 | | 10x-26=94 | | 5x+5=105-5x | | 4w-2+2(w-1)= | | 2x+5y= | | 17+3a=1 | | 5k-4-k=3k-6+2k | | 17+3=1 | | 24-x=4(x+1) | | Z^2-14z=-38 | | -8n-1.6=8 | | -126=-18a | | 4x+(-15)=9 | | 5x+38=12x-25 | | -4v-1-4+v= | | 5x+38=12x-5 |